Have vehicle emissions of primary NO2 peaked?. (18th April 2016) - Carslaw, David C.; Murrells, Tim P.; Andersson, Jon; Keenan, Matthew
Abstract : Reducing ambient concentrations of nitrogen dioxide (NO2 ) remains a key challenge across many European urban areas, particularly close to roads. This challenge mostly relates to the lack of reduction in emissions of oxides of nitrogen (NO x ) from diesel road vehicles relative to the reductions expected through increasingly stringent vehicle emissions legislation. However, a key component of near-road concentrations of NO2 derives from directly emitted (primary) NO2 from diesel vehicles. It is well-established that the proportion of NO2 ( i.e. the NO2 /NO x ratio) in vehicle exhaust has increased over the past decade as a result of vehicle after-treatment technologies that oxidise carbon monoxide and hydrocarbons and generate NO2 to aid the emissions control of diesel particulate. In this work we bring together an analysis of ambient NO x and NO2 measurements with comprehensive vehicle emission remote sensing data obtained in London to better understand recent trends in the NO2 /NO x ratio from road vehicles. We show that there is evidence that NO2 concentrations have decreased since around 2010 despite less evidence of a reduction in total NO x . The decrease is shown to be driven by relatively large reductions in the amount of NO2 directly emitted by vehicles; from around 25 vol% in 2010 to 15 vol% in 2014 in inner London, for example. The analysis of NO x and NO2 vehicle emission remote sensing data shows that these reductions have been mostly driven by reduced NO2 /NO x emission ratios from heavy duty vehicles and buses rather than light duty vehicles. However, there is also evidence from the analysis of Euro 4 and 5 diesel passenger cars that as vehicles age the NO2 /NO x ratio decreases. For example the NO2 /NO x ratio decreased from 29.5 ± 2.0% in Euro 5 diesel cars up to one year old to 22.7 ± 2.5% for four-year old vehicles. At some roadside locations the reductions in primary NO2 have had a large effect on reducing both the annual mean and number of hourly exceedances of the European Limit Values of NO2 .